2021
DOI: 10.1002/jcsm.12865
|View full text |Cite
|
Sign up to set email alerts
|

Serum Meteorin‐like is associated with weight loss in the elderly patients with chronic heart failure

Abstract: Background Unintentional weight loss (cachexia) has been associated with poor outcomes in chronic heart failure (CHF). Meteorin‐like (Metrnl) is a novel myokine with protective effects on cardiovascular diseases. However, the change of Metrnl concentrations and its role in elderly patients with CHF remains unclear. The aim of this study was to evaluate the association of serum Metrnl with weight loss and outcomes in elderly patients with CHF. Methods A total of 931 consecutive elderly patients (aged 60 years a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Recent studies showed that serum IL‐41 levels were reduced in many diseases, especially in patients with inflammation‐related diseases. Cai et al 20 found that serum IL‐41 levels were lower in chronic heart failure patients when compared to control subjects. Several studies demonstrated that serum IL‐41 levels were decreased in T2D patients compared with the healthy controls 21–23 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that serum IL‐41 levels were reduced in many diseases, especially in patients with inflammation‐related diseases. Cai et al 20 found that serum IL‐41 levels were lower in chronic heart failure patients when compared to control subjects. Several studies demonstrated that serum IL‐41 levels were decreased in T2D patients compared with the healthy controls 21–23 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, logistic regression analysis revealed that reduced circulating Metrnl levels were independently associated with increased risk of hyper-TG, hyper-TC, and hyper-LDL in the current study. Sparklingly, results from clinical studies have revealed that decreased systemic Metrnl levels are related to coronary artery disease and chronic heart failure ( 33 , 34 ). Besides, very recently, it has been indicated that the lack of Metrnl is prone to promote cardiac hypertrophy, and the overexpression or treatment of Metrnl can activate the PPARγ coactivator-1α (PGC1-α) and fatty acid oxidation (FAO) pathways of cardiomyocytes to protect heart against cardiac dysfunction in mice ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Results from experimental studies have shown that subfatin can reduce doxorubicin-induced cardiotoxicity by activating the cyclic AMP/protein kinase A/Sirtuin1 pathway, and reduce cardiomyocyte apoptosis caused by ischaemia/reperfusion injury through activation of AMP-activated protein kinase/p21-activated kinase 2 signalling ( 14 , 15 ). Cai et al showed that low serum Metrnl concentrations in elderly patients with congestive heart failure were associated with weight loss and the severity of cardiac dysfunction ( 16 ). Our results demonstrated that the sensitivity and specificity was 64% and 69%, respectively, when differentiating patients with AMI (STEMI and NSTEMI) from those without AMI, whereas the sensitivity was 94% and specificity was 41% when in differentiating STEMI from NSTEMI patients.…”
Section: Discussionmentioning
confidence: 99%